The Sichuan Mental Health Survey: Methodology - Su, Rong-cheng; Huang, Li-hong; Li, Jia; Zhou, Bo; Zhao, Jia-jun; Li, Hui (Frontiers in Psychiatry, 2021)
The Sichuan Mental Health Survey (SMHS) is a provincially representative survey with coherent methodology to obtain the prevalence of multiple mental disorders and service use, and to analyze the psychological and social risk factors or correlates in Sichuan, China. A cross-sectional design is employed to sample adults from 200 communities/villages in all 21 prefectural-level municipalities of Sichuan province in a five-stage provincially representative disproportionate stratified sampling design, which investigate the prevalence of mental disorders (anxiety disorders, mood disorders, schizophrenia and other psychotic disorders, drug-use and alcohol-use disorders, impulse-control disorder, and eating disorder). Participants need to be interviewed face to face by trained interviewers from local primary health care institutions and psychiatrists. The quality control stuffs implement data-quality control by checking records and statistics in survey system, then re-interviewing checks are done by the psychiatrists. Data is weighted to adjust the sample distribution to match the whole population. The outcomes of SMHS would demonstrate the serious challenges posed by the high burdens of mental disorders, but also offer baseline data for policy makers and health-care professionals to study and resolve the factors that influence mental health in Sichuan, China.